2018
DOI: 10.1039/c7sc05295b
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxovanadate-alkoxide clusters as multi-electron charge carriers for symmetric non-aqueous redox flow batteries

Abstract: Installation of bridging alkoxide ligands leads to improvements to solubility, stability and redox profile of POM clusters!

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
175
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(187 citation statements)
references
References 62 publications
5
175
0
6
Order By: Relevance
“…As such, we measured the solubility of 1‐L a in acetonitrile with 0.1 m [NBu 4 ][PF 6 ], thus mimicking the working conditions of a NRFB cell (Figure S4). We found the solubility of 1‐L a to be 0.214 m , a nominal increase over its homoleptic congener, 1 (0.203 m ) . Previous work has demonstrated that decreasing the symmetry of charge carrier complexes disfavors crystal packing, increasing the solubility of these compounds .…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…As such, we measured the solubility of 1‐L a in acetonitrile with 0.1 m [NBu 4 ][PF 6 ], thus mimicking the working conditions of a NRFB cell (Figure S4). We found the solubility of 1‐L a to be 0.214 m , a nominal increase over its homoleptic congener, 1 (0.203 m ) . Previous work has demonstrated that decreasing the symmetry of charge carrier complexes disfavors crystal packing, increasing the solubility of these compounds .…”
Section: Resultssupporting
confidence: 66%
“… Select examples of previously reported nonaqueous charge carriers composed of one or more transition metals. Specific attention has been called to examples that highlight synthetic strategies aimed to improve the stability and solubility of molecular redox‐active species …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Non‐innocent ligands have been prominently targeted of late, with examinations of bipyridine complexes, modified versions, and three‐coordinate hybrids . Recently, polyoxometalate complexes have been revised for nonaqueous systems, exhibiting excellent reversibility albeit with a relatively small potential …”
Section: Figurementioning
confidence: 99%
“…[13] Recently,p olyoxometalate complexes have been revisedf or nonaqueoussystems, exhibiting excellent reversibility albeit with ar elativelys mall potential. [14] Cost is the ultimate driver for RFB implementation, [15] and to meet those targets many researchers are focusingo nt he redox carriers that show very high solubilities (> 2.5 m), carry > 2electrons per molecule, and produce a > 3Vcell potential. To meet these goals, we were intrigued by the ability of aN icyclam complex to generate ac ell potential of approximately 2.5 Va nd operate in both half-reactions of the cell.…”
mentioning
confidence: 99%